A Theoretical Approach to the Transition from a Resource Based to a Knowledge-Economy - Diana Gioacasi (CES Working Papers, 2015)
Economic development and the emergence of new technologies have changed the optics on the factors that are generating added value. The transition from a resource-dependent economy to one focused on tangible non-financial factors has progressed in a gradual manner and took place under the influence of globalization and of the internet boom. The aim of this article is to provide a theoretical approach to this phenomenon from the perspective of the temporal evolution of enterprise resources.
Keywords: Q00; D83; 330; competitive advantage; resource based economy; new economy